Surgicel Mimicking Brain Abscess: A Case Report - Niyaf, Ali; Niraula, Kiran; Limbu, Chandra Prakash; Rasheed, Arusha Ali; Zauma, Aminath (Eastern Green Neurosurgery, 2021)
Hemostasis is one of the most essential measures in Neurological procedures. Surgicel (Oxidized cellulose) is one of the most frequently used hemostatic agent used worldwide during surgical procedures. We aim to present a case of radiological diagnostic dilemma of a ring enhancing brain lesion where brain abscess, intracranial hematoma and surgicelloma was identified as challenging differential diagnosis. In this paper, we present a case, where a complication occurred with the use of surgicel following craniectomy and evacuation of hematoma.